Glossopharyngeal neuralgia as a postoperative complication of tonsillectomy: a case report - Motter, Dema; Suseeharan, Melanie; Wahba, Basim (International Surgery Journal, 2022)
Tonsillectomy is one of the most common procedures performed by otolaryngologists. Post-operative complications commonly include temporary pain, infection, and bleeding. Glossopharyngeal neuralgia is a rare complication that has been previously documented in the literature. Glossopharyngeal neuralgia is a rare type of facial pain syndrome that is characterised by radiating pain in the sensory distribution of the glossopharyngeal nerve. It can cause sharp shooting pain in the face, ears and/or back of the throat. Pain is exacerbated with repetitive movements such as chewing, speaking, and swallowing. The majority of glossopharyngeal neuralgia is idiopathic in origin; however, we report a case of a 37-year-old lady that developed glossopharyngeal neuralgia immediately after tonsillectomy. Her condition was managed with intraoral injection of alcohol and saline preparation in the tonsillar fossa with good effect.